Isolation of protease from halotolerant bacteria and its purification by using aqueous two-phase system - Nur Nadiah Shuhada binti Abd Samad (Kulliyyah of Engineering, International Islamic University Malaysia, 2017)
Rising demands on proteases in various applications in industries encouraged the discovery of potent protease sources, especially from microorganisms. Proteases from fermented food have a potential to be used for industrial applications because they may produce halotolerant proteases. Halotolerant proteases can be used in the production of traditional fermented food to shorten the period of the fermentation process compared to the traditional method which took 4-6 months for natural fermentation. Moreover, high risks of protein degradation during purification due to a harsh downstream processing encourage the application of the aqueous two-phase system (ATPS) as a purification method for proteases.This study aimed to isolate and identify the bacteria strain that can produce proteases, and the aqueous two-phase system (ATPS) was applied as the protease purification method. Halotolerant bacteria were isolated from three types of protein-rich fermented food, which are fermented fish sauce (Budu), fermented fish (Pekasam) and fermented soybean (Taucu). The proteolytic activity was observed via a qualitative analysis using a skim milk agar plate. On the other hand, a quantitative analysis was performed on protease assay using casein as a substrate. Protease secreted by the isolated bacteria was concentrated using ammonium precipitation and further purified using PEG/sodium citrate system. Among the samples, only fermented fish sauce (Budu) showed a positive result with the presence of protease-producing halotolerant bacteria. The clear zone observed on skim milk agar indicated the ability of the bacteria to secrete proteolytic enzyme and degrade the casein into small fragments. B7 isolate was selected as the highest protease producer with a specific activity of (3.70±0.06 U/mg) and identified based on morphology, Biolog system and 16S rDNA sequencing. Besides, B7 isolate can also tolerate the presence of sodium chloride (NaCl) up to 10%. Hence, the B7 isolate is classified as moderately halotolerant bacteria. The results indicated that B7 isolate has a 98% similarity with Bacillus amyloliquefaciens subs. plantarum FZB42 strain. Thus, the B7 isolate was named Bacillus amyloliquefaciens B7 strain. The results of the Biolog analysis also confirm this result. The One factor at time (OFAT) design was employed to determine the central point for each ATPS parameter which resulted in the highest value of responses for enzyme activity, specific activity, and purification factor. Parameters involved in OFAT analysis are molecular weight of polyethelene glycol (PEG), type of salts, concentration of PEG and salt, pH and temperature. Optimization of ATPS conditions based on the face-centered central composite design (FCCCD) in response surface methodology (RSM) with 11 runs showed that the optimal conditions for ATPS are 27% (w/w) PEG 1500, 34% (w/w) sodium citrate, at pH 7 and a temperature of 35 oC. Analysis of variance (ANOVA) showed the coefficient with determination (R2) were 0.9546, 0.9465 and 0.9465 for enzyme activity, specific activity and purification factor, respectively. Lastly, the molecular weight of the purified protease was identified as 40 kDA based on sodium dodecyl sulphate-polyacrylamide gel electrophoresis (SDS-PAGE) analysis. In conclusion, the isolation of Bacillus amyloliquefaciens B7 strain from Budu as a protease producer and the aqueous two-phase system as a suitable protease purification method show the great potential for advancement in the industrial enzyme.